Anaesthesia management for acute appendicitis in cases with Sjögren's syndrome accompanying autoimmune hepatitis - Demirel, Ismail; Ozer, Ayse Belin; Bayar, Mustafa K.; Erhan, Omer L. (My University, 2013)
Characterised by lymphocytic infiltration of exocrine glands, Sjögren's syndrome (SS) is a chronic autoimmune disease. Symptoms belonging to the involved systems may occur owing to the fact that it affects multiple systems. While rheumatoid arthritis is observed concomitantly, its co-occurrence with autoimmune hepatitis is astonishingly common. Through this case report, we intended to review issues that should be attended to while administering anaesthesia to a patient with SS accompanying autoimmune hepatitis. In the light of literature, we aimed to discuss anaesthesia management to the patient with SS and issues stemming from the clinical features of SS. In SS, the expected issues are liver problems related autoimmune hepatitis and respiratory problems related pulmonary fibrosis. A careful preoperative evaluation, a comprehensive preparation against difficulty in intubation, a selective anaesthesia management in terms of autoimmune hepatitis and close monitoring of postoperative respiration may prevent or decrease possible complications. Copyright 2013 BMJ Publishing Group. All rights reserved.
Keywords: azathioprine; budenofalk; cisatracurium; desflurane; oxygen; propofol; remifentanil; ursodeoxycholic acid; acute appendicitis; adult; anesthesia; anesthesia induction; appendectomy; article; autoimmune hepatitis; case report; endotracheal intubation; female; hospital discharge; human; ischemic heart disease; laryngoscopy; loading drug dose; nausea and vomiting; preoperative evaluation; priority journal; recovery room; Sjoegren syndrome; stomach pain; xerostomia